African Islands : Leading Edges of Empire and Globalization - Sanchez, Danielle Porter, 1986-; Parrott, R. Joseph, 1985-; Falola, Toyin (Book collections on Project MUSE., 2019)
Explores the culturally complex and cosmopolitan histories and of islands off the African coast.